Public Procurement Law regulating e-procurement, a reform tool for Lebanon - Bou-Ghanem, Diana (Technium Social Sciences Journal, 2022)
Between 2019 and 2021, the public procurement systems in Lebanon was under study as a first step to undergo a critical reform process. This process was topped with the issuance of the Public Procurement Law number 244 on July 2021. There are great hopes built on this law since it has been long waited for and the prospects on its success are high. It is based on eight principles: integration, transparency, competitiveness, efficiency, accountability, integrity, professionalism, and sustainability and local development. The law creates a regulatory agency, an independent body to handle complaints, encourages SMEs and local industry among other benefits. The objective of this paper is to define the effectiveness and validity of the new Law and e-procurement stipulated in the new Law and how is it a tool for reform that enhances transparency integrity and efficiency in the new Lebanese procurement system. The Methodology in this paper is a qualitative literature review and document analysis of existing reports from the Lebanese official entities and international bodies that took part in the assessment and preparation of the new Public Procurement.